Manajemen Kesan melalui Prestasi Sekolah SDN Kemakmuran 1 Songgom Brebes: Kajian Dramaturgi terhadap Branding Lembaga Pendidikan di Indonesia - Ikrimatul Aola; Muh. Hanif (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
This article aims to examine how impression management through school achievement of SDN Kemakmuran 1 Songgom Brebes: a dramaturgical study of branding educational institutions in Indonesia. The research method used is qualitative with interview data collection techniques with the principal, teachers and students, as well as direct observation of the learning process and study documentation. This study attempts to examine the dramaturgical theory of impression management through school achievement of SDN Kemakmuran 1 Songgom Brebes towards branding educational institutions in Indonesia. The results of the study indicate that the impression management of SDN Kemakmuran 1 through its achievements towards branding educational institutions in Indonesia is by collaborating with various parties both internally and externally and establishing a wide communication channel. In addition, there are several supporting factors and inhibiting factors but do not reduce school achievement.